Peran Pemasaran Hijau dalam Membentuk Preferensi Konsumen Generasi Z - Cempaka Murti, Anggun; Arqy Ahmadi, Mirzam (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The aim of this research is to explore how green marketing influences consumer preferences, especially Generation Z, which is known to have higher concern for the environment. The research uses qualitative methods with a literature review as the main approach. Data was obtained from various secondary sources such as scientific journals, books and research reports. The research results show that green marketing has an important role in shaping Gen Z's purchasing preferences. The main factors influencing their preferences include environmental awareness, the influence of reference groups through social media, and the combination of environmental and health values ​​in products. Gen Z tends to prefer products that are environmentally friendly and support their health. Although they are willing to pay more for green products, affordability remains an important consideration. This research emphasizes the importance of an effective green marketing strategy, which can utilize social media and balance price and quality aspects to attract the attention of Gen Z consumers